2018
DOI: 10.3168/jds.2017-12710
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty assessment of the breath methane concentration method to determine methane production of dairy cows

Abstract: The breath methane concentration method uses the methane concentrations in the cow's breath during feed bin visits as a proxy for the methane production rate. The objective of this study was to assess the uncertainty of a breath methane concentration method in a feeder and its capability to measure and rank cows' methane production. A range of controlled methane fluxes from a so-called artificial reference cow were dosed in a feed bin, and its exhaled air was sampled by a tube inside the feeder and analyzed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…The study by van Engelen et al (2018) obtained records in the Lely A4 Astronaut (Lely, Maassluis, the Netherlands), which has a more open feeding bin than the Delaval AMS used in our study. One possibility is the dilution of gases due to differences in feed bin dimensions or in environmental factors, such as variable wind speed between installations (Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The study by van Engelen et al (2018) obtained records in the Lely A4 Astronaut (Lely, Maassluis, the Netherlands), which has a more open feeding bin than the Delaval AMS used in our study. One possibility is the dilution of gases due to differences in feed bin dimensions or in environmental factors, such as variable wind speed between installations (Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Methane traits as defined in our study reflect "pure" CH 4 emissions, whereas CH 4 predictions by Chagunda et al (2009b) depend on body trait or physiological characteristics. Hence, in quantitative genetic studies, and following a deterministic CH 4 prediction strategy, the estimated heritability does not fully reflect the individual CH 4 genetic background (Yin et al, 2015). In genome-wide association studies, Manzanilla-Pech et al (2016) found an overlap for 19 % of SNP markers being significantly associated with DMI, body weight and individual CH 4 production in dairy cattle.…”
Section: Strategies Of Ch 4 Trait Definitionsmentioning
confidence: 99%
“…In such a context, approaches based on feed supplements were unsuitable under grazing conditions (Baker, 1999). Predictions of CH 4 via deterministic modeling usually require a large amount of input data, e.g., DMI, dietary or milk components, which are difficult to record (Kabreab et al, 2006;Yin et al, 2015). Further indirect methods for CH 4 emission predictions based on the ruminal microbiome composition but associations between CH 4 production and microbiome characteristics were inconsistent (Shi et al, 2014;Ellison et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to effects of external conditions, sniffer methane measurements are affected by random errors such as those caused by differences in sampling distance and the cow's head movement (e.g., Wu et al, 2018). These are indeed factors that will increase variation in sniffer methane measurements.…”
mentioning
confidence: 99%
“…For example, cows showing restless behavior during milking, which is partly due to genetic differences between cows, might have lower sniffer methane levels because of sampling distance. Knowledge of variation in sniffer methane measurements due to such systematic errors is limited and certainly requires further investigation, as was pointed out by Wu et al (2018). However, even if genetic differences in sniffer methane partly reflect differences in other traits, this does not disqualify the use of sniffer methane measurements for selective breeding.…”
mentioning
confidence: 99%